2006
DOI: 10.1002/imhj.20095
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression: A review of relevant treatment approaches for mothers and infants

Abstract: The negative impact of postpartum depression on the mother-infant relationship and infant development more generally has been well documented. Compared to infants of nondepressed mothers, infants of depressed mothers have been shown to be less securely attached to their caregivers and often have cognitive, emotional, and behavioral deficits that persist well into childhood. Recent evidence has suggested that reduction of maternal depressive symptoms may itself not be sufficient to prevent negative effects on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 29 publications
(33 reference statements)
3
115
0
7
Order By: Relevance
“…Depressed mothers' early parenting, specifically their insensitivity to infant cues and inability to provide effective emotional regulation, has been suggested as an important mechanism in the development of insecure or disorganized infant-mother attachment and subsequent reduced social competence and increased behavior disorders (Ashman & Dawson, 2002;Braungart-Rieker, Garwood, Powers, & Wang, 2001;Martins & Gaffan, 2000). A variety of interventions, including clinic-based and home-visiting approaches, have been developed to attempt to provide distressed mothers with effective treatment and support (Cooper & Murray, 1998;Holden, Sagovsky, & Cox, 1989); however, a recent review of treatments found that the reduction in maternal depressive symptoms achieved by home-visiting and psychotherapy programs may not be sufficient to prevent negative effects of maternal depression on children (Nylen, Moran, Franklin, & O'Hara, 2006). By contrast, treatments targeting the mother-infant relationship showed an improvement in attachment security and infant cognitive functioning which, in some cases, occurred without concomitant reduction in depressive symptoms (Nylen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depressed mothers' early parenting, specifically their insensitivity to infant cues and inability to provide effective emotional regulation, has been suggested as an important mechanism in the development of insecure or disorganized infant-mother attachment and subsequent reduced social competence and increased behavior disorders (Ashman & Dawson, 2002;Braungart-Rieker, Garwood, Powers, & Wang, 2001;Martins & Gaffan, 2000). A variety of interventions, including clinic-based and home-visiting approaches, have been developed to attempt to provide distressed mothers with effective treatment and support (Cooper & Murray, 1998;Holden, Sagovsky, & Cox, 1989); however, a recent review of treatments found that the reduction in maternal depressive symptoms achieved by home-visiting and psychotherapy programs may not be sufficient to prevent negative effects of maternal depression on children (Nylen, Moran, Franklin, & O'Hara, 2006). By contrast, treatments targeting the mother-infant relationship showed an improvement in attachment security and infant cognitive functioning which, in some cases, occurred without concomitant reduction in depressive symptoms (Nylen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of interventions, including clinic-based and home-visiting approaches, have been developed to attempt to provide distressed mothers with effective treatment and support (Cooper & Murray, 1998;Holden, Sagovsky, & Cox, 1989); however, a recent review of treatments found that the reduction in maternal depressive symptoms achieved by home-visiting and psychotherapy programs may not be sufficient to prevent negative effects of maternal depression on children (Nylen, Moran, Franklin, & O'Hara, 2006). By contrast, treatments targeting the mother-infant relationship showed an improvement in attachment security and infant cognitive functioning which, in some cases, occurred without concomitant reduction in depressive symptoms (Nylen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…An emerging consensus suggests that promoting the emerging mother-child relationship increases the likelihood of resilient trajectories for both mothers and babies (Als et al, 2003;Beeghly et al, 1995;Browne & Talmi, 2005;. While individual psychotherapy and psychotropic medications have been used effectively to address PPD (National Research Council and Institute of Medicine, 2009), treatments that focus on improving the mother-infant relationship may have greater potential to reduce symptoms (Paris, Bolton, & Spielman, 2011;Forman et al, 2007;Nylen, & Moran, Franklin, & O'Hara, 2006).…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Accumulated evidence clearly demonstrates the importance of early mother-infant and father-infant interactions to development (Armstrong, Fraser, Dadds, & Morris, 2000;BakermansKranenburg et al, 2005;Bates & Dozier, 2002;Lyons-Ruth, Connell, Grunebaum, & Botein, 1990;Nylen, Moran, Franklin, & O'Hara, 2006;Wan & Green, 2009). Ideally, these early interactions forge an attachment that promotes a child's security, safety, and affective regulation (Bowlby, 1982;Schore, 2001) where the child comes to recognize an adult as a reliable source of safety and love (Saakvitne, Tennen, & Affleck, 2003).…”
Section: Attachment and Relational Traumamentioning
confidence: 99%